2010
DOI: 10.1007/s11845-010-0582-3
|View full text |Cite
|
Sign up to set email alerts
|

Demographics, nature and treatment of orthopaedic trauma injuries occurring in an agricultural context in the West of Ireland

Abstract: There were significantly (P < 0.01) more male than female farmers (73 vs. 27%) with a mean age of 63 years (ranging from 13 to 87 years). Average number of out-patient visits related to the injury was 3.6. Injuries involving livestock resulted in the majority of accidents (P < 0.05) with a significant rise in the number of visits with increasing age (P < 0.01) with older patients having more severe injuries. Soft tissue injuries and fractures were commonly encountered. Complex fractures were the slowest injury… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 3 publications
0
7
0
1
Order By: Relevance
“…In small scale, nonmechanized farming such as that practiced by the Amish, injuries from falls, kicks from livestock, interactions with farming equipment, and other farm-chore related encounters account for 58.3% of observed fractures (Jones, 1990). Domestic animals are a commonly cited source of injury, accounting for over 65% of the farm-related injuries reported in several clinical studies (Byrne et al, 2011;Drudi, 2000;Virtanen et al, 2003). When injuries are evaluated by farm type, Virtanen et al (2003) found that falls and entanglement in objects are the most common causes of injury among pig, poultry, and crop farmers, while being kicked, pushed, or trampled is most common among farmers specializing in cattle.…”
Section: Traumatic Injury and Agriculturementioning
confidence: 99%
See 2 more Smart Citations
“…In small scale, nonmechanized farming such as that practiced by the Amish, injuries from falls, kicks from livestock, interactions with farming equipment, and other farm-chore related encounters account for 58.3% of observed fractures (Jones, 1990). Domestic animals are a commonly cited source of injury, accounting for over 65% of the farm-related injuries reported in several clinical studies (Byrne et al, 2011;Drudi, 2000;Virtanen et al, 2003). When injuries are evaluated by farm type, Virtanen et al (2003) found that falls and entanglement in objects are the most common causes of injury among pig, poultry, and crop farmers, while being kicked, pushed, or trampled is most common among farmers specializing in cattle.…”
Section: Traumatic Injury and Agriculturementioning
confidence: 99%
“…Agricultural occupations are ranked among the ten most dangerous professions in the modern world and a significant cause of traumatic injury in humans (Bureau of Labor Statistics, 2015; Jones, 1990;Virtanen, Notkola, Luukkonen, Eskola, & Kurppa, 2003). Clinical studies largely attribute farm-related injuries to accidents involving farm equipment, falls and encounters with animals, but also reveal great variability in how much each factor contributes to the overall pattern in different populations (Byrne et al, 2011;Cogbill, Steenlage, Landercasper, & Struee, 1991;Drudi, 2000;Jones, 1990;Myers et al, 2009;Nordstrom et al, 1995;Pickett et al, 1995;Purschwitz & Field, 1990;Stallones, 1990;Virtanen et al, 2003;Von Essen & McCurdy, 1998). In small scale, nonmechanized farming such as that practiced by the Amish, injuries from falls, kicks from livestock, interactions with farming equipment, and other farm-chore related encounters account for 58.3% of observed fractures (Jones, 1990).…”
Section: Traumatic Injury and Agriculturementioning
confidence: 99%
See 1 more Smart Citation
“…Prevention of agricultural work-related injuries is crucial. The use of protective clothing, appropriate guards for dangerous parts, enforcement of the provision of safeguard in all farm equipment, better education and safety precaution have been proposed, accompanied by the appropriate design of rural trauma and emergency protocols [5,7,[9][10][11].…”
Section: Preventionmentioning
confidence: 99%
“…Farmyard injuries affect all age groups of farmers. Especially over 55 years greater risk of serious injury than their younger counterparts was found [4][5][6]. Farmyard injuries in young adults and the elderly usually result from machinery accidents, whereas children tend to be injured by animals, runovers and motor vehicle collisions [7].…”
mentioning
confidence: 99%